IMPLEMENTASI MODEL WATERFALL PADA PEMBANGUNAN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMK YAPIPA SERPONG UTARA - Nurajijah Nurajijah; Karlena Indriani (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2017)
The school is the technical implementation of formal education that is expected to follow the development of science in the field of information technology. The use of internet media by teachers and students in SMK YAPIPA North Serpong is only limited to locate the material or the task of the student and friendship social media. Delivery of academic information is still done the conventional and do not optimally use information technology. A website is a right choice to implement a system of academic information that is designed using PHP and HTML programming language and MySQL database as data storage. Academic information system website based to facilitate the school in conveying academic information and can be accessed anytime and anywhere